Marine Ecotourism Development Strategy at Tiram Beach, Padang Pariaman Regency, West Sumatra Province - Febri Naldi; Dessy Yoswaty; Irvina Nurrachmi (Faculty of Fisheries and Marine, Universitas Riau, 2024)
The research was conducted in February-April 2024 at Tiram Beach, Padang Pariaman Regency, West Sumatra Province. The aims and benefits of the study are to identify the potential and objects that need to be developed at Tiram Beach as a marine ecotourism area, to find out the public's perception of ecotourism activities at Tiram Beach, to formulate a strategy for developing marine ecotourism at Tiram Beach to support sustainable tourism. The research method used was a survey. Research carried out in the field includes measuring water quality and aiming to see the level of water quality, temperature, brightness, salinity, pH, and current speed to support marine ecotourism on Tiram Beach. After that, the respondents were selected: 20 tourists, 20 local communities, 15 business actors, and ten policymakers. Based on the Suitability Index, Tiram Beach is in the S1 category (very suitable) with a score of 75%, and it is to be used as marine ecotourism by observing 10 IKW parameters. Based on the development strategy using SWOT analysis through field observations, strength results were obtained, including restaurants' international standard public toilets; weakness covers: lack of development breakwater in the area of ​​coastal tourist locations and lack of creativity from business actors, opportunity includes: the existence of objects that affect the welfare of local communities which can be used to increase income through buying and selling activities and services for visiting tourists, Threats includes: environmental changes that will affect the continuation of ecotourism on Tiram Beach, ecological degradation caused by humans